Housing Accessibility Constraints amongst Public Servants in Ogun State Nigeria - A Case of Ota, Ogun State - Orekan, Orekan; Adebimpe, Atinuke (International Journal of Property Sciences (E-ISSN: 2229-8568), 2018)
This study examined the constraints in housing ownership amongst public servants in Ota, Ogun State. The work specifically sought to find the factors that could affect housing accessibility among target population in the study area. In achieving the aim of the study, survey was conducted among the selected population which was later confirmed with interviews. The causative factors of housing constraints were tested with the use of one-way ANOVA to test the significant difference in the response of the respondents and POST- HOC was used in the ranking of these factors. It was revealed that finance and institutional impediments are the two major factors amongst others that affect housing accessibility in the study area among public workers. Narrative and descriptive research designs in form of tables, bar charts and theoretical analysis were adopted. The study thus recommends that mortgage institutions and finance houses to have a special consideration and arrangement to public servants and low-income earners so as to increase of descent residential properties in major cities in Nigeria.